2015
DOI: 10.1002/adfm.201501394
|View full text |Cite
|
Sign up to set email alerts
|

Does Electronic Type Matter when Single‐Walled Carbon Nanotubes are Used for Electrode Applications?

Abstract: © 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Single-walled carbon nanotube (SWNT) electrodes that are chemically and mechanically robust are fabricated using a simple drop cast method with thermal annealing and acid treatment. An electronic-type selective decrease in sheet resistance of SWNT electrodes with HNO3 treatment is shown. Semiconducting SWNTs show a significantly higher affinity toward hole doping in comparison to metallic SWNTs; a ≈12-fold and a ≈fivefold drop in sheet resistance, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Cost-effective solutions for the ITO replacement have been actively sought after as well, using other oxides (e.g., FTO or AZO), CNTs, 1168 metal mesh or nanowires, 1169−1173 and other materials. 1174,1175 For example, Kim et al 1169 ature roll-to-roll sputtering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost-effective solutions for the ITO replacement have been actively sought after as well, using other oxides (e.g., FTO or AZO), CNTs, 1168 metal mesh or nanowires, 1169−1173 and other materials. 1174,1175 For example, Kim et al 1169 ature roll-to-roll sputtering.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effective solutions for the ITO replacement have been actively sought after as well, using other oxides (e.g., FTO or AZO), CNTs, metal mesh or nanowires, and other materials. , For example, Kim et al reported a Cu 2 O/Cu/Cu 2 O multilayer mesh electrode grown by room-temperature roll-to-roll sputtering. They demonstrated a low sheet resistance of ∼15 Ohm/square, high optical transmittance of ∼89%, and good mechanical flexibility.…”
Section: Applicationsmentioning
confidence: 99%
“…Numerous reports have shown that stand-alone CNTs can act as good electrodes in solar cells, with efficiency ranging from 4.4% to 6.32% (Table ). A hybrid graphene/CNT electrode has lower charge-transfer resistance with the electrolyte (20 times smaller than for platinum-based cathodes) owing to its large surface area. DSSCs utilizing this flexible, vertically aligned CNT/graphene hybrid cathode out­performed Pt-based cells in both rigid (8.2% vs 6.4%) and flexible (3.9% vs 3.4%) assemblies.…”
Section: Graphene Schottky Barrier Cellsmentioning
confidence: 99%
“…These materials are frequently treated and modified [43][44][45][46][47][48]. Other common electrode materials are tungsten oxide [49][50][51] or materials based on graphene [52,53] and nanotubes [54][55][56]. The second electrode is usually made of metal [57][58][59].…”
Section: Introductionmentioning
confidence: 99%